Penerapan Algoritma Pemrograman dalam Pembelajaran Ilmu Komputer - Pinkan Indriani Daulay; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Algorithms are at the core of computer science and play an important role in computer programming. Programming aims to tell the computer to perform certain functions. Computer instructions provide a set of instructions written in a language that the computer can understand. Programming algorithms consist of various detailed sequential steps aimed at solving various computer programming problems. A computer is an electronic device capable of receiving, processing, storing and creating information. In general, a computer is a machine that is used to perform various tasks, such as data processing, calculations, storing information, and executing predefined programs. Computers are divided into two parts, namely hardware and software which work together to support various types of computers and applications. Some applications of algorithms in computer science learning are data compression algorithms, binary search algorithms, linear search algorithms, repetition algorithms and hashing algorithms. When writing and creating an algorithm, you don't really focus on the programming language, so there are lots of algorithms used in programming. The purpose of this scientific work is to find out how important it is to apply programming algorithms in computer science learning. In order to achieve this goal, a literature study research method was carried out.